Popping off a phenomenological analysis of the lived marginalization of drag queens in the Philippines - Lasota, Clark Zeigfred I.
The study explored the lived experiences of drag queens in conjunction with how they defined their craft, the marginalization they experienced, and their coping strategies. Through the use of Interpretative Phenomenological Analysis (IPA), six self-identified drag queens were interviewed in the Philippines. Results showed that drag is considered both as a profession and an art form and was further highlighted through mainstream shows, which shed light on their stories and opened up opportunities. However, despite this recognition, drag queens are subjected to intersectional marginalization from outside the LGBTQ community and also from its members, presenting a "double stigma" that produces additional struggles. This resulted in discrimination, violence, and possible exploitation and the existence of segregation inside the LGBTQ community thus resulting in difficulty in establishing romantic relationships. Drag has served as a tool for social change, and empowerment, and in creating communities that serve as their support system and confidants. Drag queens have always questioned the status quo on gender and expression, and incorporated protest within their performances, raising specific causes and championing their advocacies. This study sheds light on the multifaceted experiences of drag queens in the Philippines and emphasizes the importance of understanding and addressing their unique challenges. As experiences of marginalization are explored and unpacked, the researchers hope to bring gradual changes in the social and political scene.